2017
DOI: 10.21595/vp.2017.19238
|View full text |Cite
|
Sign up to set email alerts
|

Modern suspension systems for automotive vehicles and their test methods

Abstract: Abstract. This article provides a discussion on various solutions used in modern suspension systems of automotive vehicles. The mechanical dependent suspension system and some solution of adaptive, semi-active and active suspension system has been described. The paper also presents shortly test methods used to evaluation of technical conditions of this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Luis Carvalho et al suggested a technique based on computing the ratio of signals acquired in frequency domain for both fault and healthy conditions to assess the condition of the tie rod ball joint used in the automobile suspension. 10 From the above literatures one can understand that these type of data-driven methods required domain expertise and specific laboratory setup (simulation platform) to perform fault diagnosis. So nowadays researchers shift their focus toward machine learning based on data-driven approach as an alternative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luis Carvalho et al suggested a technique based on computing the ratio of signals acquired in frequency domain for both fault and healthy conditions to assess the condition of the tie rod ball joint used in the automobile suspension. 10 From the above literatures one can understand that these type of data-driven methods required domain expertise and specific laboratory setup (simulation platform) to perform fault diagnosis. So nowadays researchers shift their focus toward machine learning based on data-driven approach as an alternative.…”
Section: Introductionmentioning
confidence: 99%
“…13 Most of the research compares model-based methods to assess the condition of the component with a mathematical model. Identifying suitable parameters to design mathematical models for each component is tedious and difficult. Limited numbers of literature were reported that use machine learning techniques in fault diagnosis of a suspension system. Numerous research works on fault diagnosis of suspension system using vibration signal requires vibrating platform to induce forced vibration to the component. 10 Assessment of multiple fault occurrences in the suspension system was not attempted. Considering the aforementioned reasons, one can state that there is a definite need for fault diagnosis in the suspension system. Additionally, the fault diagnosis technique must be nondestructive (without the need for dismantling) and eliminate the need for a vibrating platform.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the vibration and oscillation of the suspension system using on the vehicle has been done during the last time. Konieczny and Burdzik (2017) introduced suspension system models, including the passive suspension system, the active suspension system, and the semi-active suspension system. This assessment was also commented on by Xue et al (2011) in their paper.…”
Section: Introductionmentioning
confidence: 99%
“…Dampers have a marked effect on how well tyres follow a road surface. They damp the natural bounce over the road and reduce spring oscillations (Konieczny and Burdzik, 2017). New configurations can be added to the passive suspension system to be a controlled suspension: active; or semi-active.…”
Section: Introductionmentioning
confidence: 99%